Análisis comunicacional y su relación con la práctica de valores en jovenes del sector las acacias de la Cooperativa Atilio Vélez Aray, cantón El Empalme, año 2021 - Fuentes Coello, Stefanie Jazmin (2021)
This research was carried out in El Empalme, in the Las Acacias sector of the Atilio Vélez Aray cooperative, with the objective of analyzing how the communicational analysis is related to the practice of values in young people in the sector. Through communication we can guide young people to practice values, and for that to happen, communication must be worked from home. Communication is considered as a process for the formation of values. To carry out this project, two study variables were investigated, to develop this research the survey technique was used, which was carried out online using an instrument developed in Google forms, this in order to collect more information than help meet the research objectives. The application of this survey showed that half of the young people surveyed in the Las Acacias sector do maintain communication with their parents, while a third only sometimes have a dialogue with them. And in turn if there are values that are being lost. That is why this study was carried out, which is essential for the training of young people, learning to communicate is essential from an early age and doing it correctly will determine our lifestyle.